SNG based energy storage systems with subsurface CO2 storage. (27th May 2022) - Fogel, Stefan; Yeates, Christopher; Unger, Sebastian; Rodriguez-Garcia, Gonzalo; Baetcke, Lars; Dornheim, Martin; Schmidt-Hattenberger, Cornelia; Bruhn, David; Hampel, Uwe
Abstract : Power-to-gas-to-power technologies incorporating electrolysis, methanation, SNG-fired Allam cycles and subsurface storages allow for a confined and circular use of CO2 /CH4 and thus an emission-free seasonal storage of intermittent renewable energy. Abstract : Large-scale energy storage plants based on power-to-gas-to-power (PtG–GtP) technologies incorporating high temperature electrolysis, catalytic methanation for the provision of synthetic natural gas (SNG) and novel, highly efficient SNG-fired Allam reconversion cycles allow for a confined and circular use of CO2 /CH4 and thus an emission-free storage of intermittent renewable energy. This study features a thorough technology assessment for large-scale PtG–GtP storage plants based on highly efficient sCO2 power cycles combined with subsurface CO2 storage. The Allam cycle employs supercritical CO2 as working fluid as well as an oxy-combustion process to reach high efficiencies of up to 66%. The entire PtG–GtP process chain assessed in this study is expected to reach maximum roundtrip efficiencies of 54.2% (with dedicated and sufficient O2 storage) or 49.0% (with a dedicated air separation unit). The implementation of said energy storage systems into existing national energy grids will pose a major challenge, since they will require far-reaching infrastructural changes to the respective systems, such as extensive installations of renewable generation and electrolysis capacities as well as sufficient subsurface storage capacities for both CO2 and CH4 . Therefore, this study incorporates an assessment of the present subsurface storage potential for CO2 and CH4 in Germany. Furthermore, a basic forecast study for the German energy system with an assumed mass deployment of the proposed SNG-based PtG–GtP energy storage system for the year 2050 is conducted. In case of a fully circular use of CO2 /CH4, when electricity is solely generated by renewable energy sources, 736 GW of renewables, 234 GW of electrolysis and 62 GW of gas-to-power capacities are required in the best case scenario in 2050. The total storage volume on the national scale of Germany for both CO2 and CH4 was determined to be 7.8 billion N m 3, respectively, leading to a CH4 storage capacity of 54.5 TW h. The presented investigations illustrate the feasibility of large-scale energy storage systems for renewable electricity based on high temperature electrolysis, catalytic methanation and Allam power cycles paired with large subsurface storages for CO2 and CH4 .